2011
DOI: 10.1089/tmj.2010.0098
|View full text |Cite
|
Sign up to set email alerts
|

Users and Nonusers of University-Based Dermatology Services Following a Teledermatology Encounter: A Retrospective Descriptive Analysis

Abstract: Our study describes the features, such as demographics and case-mix, of users and nonusers of university-based dermatology clinics after teledermatology encounters that may be important considerations for future evaluations of teledermatology consult systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[9][10][11] Numerous studies [12][13][14][15][16] have demonstrated acceptable diagnostic accuracy from teledermatology consultations when compared with conventional in-person office visits; however, few studies [17][18][19][20] have examined clinical outcomes of teledermatology delivery. Studies [21][22][23][24] evaluating the use of teledermatology to provide general consultation and skin cancer management have shown equivalence of outcomes with traditional office visits. Teledermatology may be an effective platform through which patients' therapy can be managed successfully by remote specialist consultation.…”
Section: T Elemedicine Is An Evolv-mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Numerous studies [12][13][14][15][16] have demonstrated acceptable diagnostic accuracy from teledermatology consultations when compared with conventional in-person office visits; however, few studies [17][18][19][20] have examined clinical outcomes of teledermatology delivery. Studies [21][22][23][24] evaluating the use of teledermatology to provide general consultation and skin cancer management have shown equivalence of outcomes with traditional office visits. Teledermatology may be an effective platform through which patients' therapy can be managed successfully by remote specialist consultation.…”
Section: T Elemedicine Is An Evolv-mentioning
confidence: 99%
“…The findings from this study corroborate those from previous telemedicine studies 18,25,26 evaluating changes in clinical outcomes in dermatology, endocrinology, psychiatry, and pediatric weight management. Other investigations 23 have evaluated outcome measures and factors related to use of conventional vs teledermatology follow-up care subsequent to teledermatology evaluation; our study specifically evaluated the impact of LI teledermatology on patient care and clinical status. Nearly 70% of our patients experienced a change in diagnosis, and more than 97% of our patients experienced changes in disease management as a result of the teledermatologist evaluation.…”
Section: Commentmentioning
confidence: 99%
“…VCs increase the possibility for ‘just in time diagnosis’ from specialist when there is no waiting time for visit by referral. It has been used in different settings and contexts in health care, for example, ophthalmology (Bergua et al ., 2009), endocrinology/diabetes management (Nikkanen et al ., 2008), cardiology (Boman et al ., 2009), dermatology (Edison et al ., 2011), and in psychiatry (Stain et al ., 2011). Another example is when a patient asks for a second opinion from another specialist physician (Törnqvist et al ., 2000; Visser et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first of the U.S. studies was a descriptive analysis (n = 1,307) of a hybrid teledermatology system in a statewide network in Missouri. 46 It was aimed at estimating the volume and proportion of teledermatology encounters that resulted in clinic visits. Between 2001 and 2007, 56 (or 4.3% of patients) were seen at the universitybased clinic after the teledermatology consult.…”
Section: Feasibility and Acceptancementioning
confidence: 99%